Identification of putative noncanonical driver mutations in patients with essential thrombocythemia. (14th March 2023) - Arai, Akihiko; Yoshimitsu, Makoto; Otsuka, Maki; Ito, Yoshikiyo; Miyazono, Takayoshi; Nakano, Nobuaki; Obama, Kosuke; Nakashima, Hidetoshi; Hanada, Shuichi; Owatari, Satsuki; Nakamura, Daisuke; Tokunaga, Masahito; et al.
Abstract: Essential thrombocythemia (ET) cases without canonical JAK2, CALR, or MPL mutations, that is, triple‐negative (TN) ET, have been found in 10%–20% of ET cases. Owing to the limited number of TN ET cases, its clinical significance remains unclear. This study evaluated TN ET's clinical characteristics and identified novel driver mutations. Among 119 patients with ET, 20 (16.8%) had no canonical JAK2/CALR/MPL mutations. Patients with TN ET tended to be younger and had lower white blood cell counts and lactate dehydrogenase values. We identified putative driver mutations in 7 (35%): MPL S204P, MPL L265F, JAK2 R683G, and JAK2 T875N were previously reported as candidate driver mutations in ET. Moreover, we identified a THPO splicing site mutation, MPL *636Wext*12, and MPL E237K. Four of the seven identified driver mutations were germline. Functional studies on MPL *636Wext*12 and MPL E237K revealed that they are gain‐of‐function mutants that increase MPL signaling and confer thrombopoietin hypersensitivity with very low efficiency. Patients with TN ET tended to be younger, although this was thought to be due to the inclusion of germline mutations, hereditary thrombocytosis. Accumulating the genetic and clinical characteristics of noncanonical mutations may help future clinical interventions in TN ET and hereditary thrombocytosis.